Financial Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
This paper applied a quantitative research design to explore the nature of burial society stokvels in South Africa. Furthermore, the benefits accruing to members were examined. Prior studies have generally focused on mobilization of savings from households through stokvels. None have paid particular attention to the nature and benefits of participating in burial society stokvels as a conduit for savings mobilisation. This study attempts to fill this gap by using a self-administered research questionnaire on a sample of 386 respondents. Members of stokvels were surveyed from the cities of Pretoria and Johannesburg in the Gauteng province of South Africa. Data was analysed using descriptive statistics, exploratory factor and correlation analyses. The study found that more females than males participated in stokvels. Results show that burial society stokvels succeed due to their informal nature, which is characterised by a lack of lengthy and stringent formalities and low transaction costs when compared to formal financial institutions. The results also show that burial society’s stokvels empower women through providing opportunities for savings. Bereaved members are able to give their deceased loved ones through the financial support obtained from the burial society stokvels. Disbursement of funds is quick due to lack of lengthy formalities found in formal insurance companies. The results show that household consumers of financial services such as funeral policies, seek speed and convenience when selecting service providers. Thus, the findings of this study have policy implications for formal financial institutions when designing products for the low end market.